Renzhu Ointment Regulates L-Type Voltage-Dependent Calcium Channel in Mice Model of Senna-Induced Diarrhea by Transdermal Administration - Zhong L; Cao X; Li L; He Y; Liu Y; Chen W; Yang F; Xiao N; Zhang J; He H (Dove Medical Press, 2023)
Lian Zhong,1,* Xiaoyu Cao,2,* Li Li,1 Yuanyuan He,1 Yanxia Liu,1 Weiwei Chen,1 Fuzhen Yang,1 Ni Xiao,1 Jun Zhang,1 Huifen He3 1School of Pharmaceutical Sciences, Guangzhou University of Chinese Medicine, Guangzhou, 510006, People's Republic of China; 2School of Chinese Materia Medica, Guangdong Pharmaceutical University, Guangzhou, 510006, People's Republic of China; 3The First Affiliated Hospital, Guangzhou University of Chinese Medicine, Guangzhou, 510405, People's Republic of China*These authors contributed equally to this workCorrespondence: Huifen He, The First Affiliated Hospital, Guangzhou University of Chinese Medicine, Guangzhou, 510006, People's Republic of China, Tel +86-15920174486, Email 15920174486@163.com Jun Zhang, School of Pharmaceutical Sciences, Guangzhou University of Chinese Medicine, Guangzhou, 510006, People's Republic of China, Tel +86-020-39356997, Email zhangjun@gzucm.edu.cnPurpose: In China, herbal preparation is commonly administered transdermally for treating pediatric diarrhea. However, few studies have probed into their antidiarrheal mechanisms. This study was designed to investigate the antidiarrheal effect of Renzhu ointment (Renzhuqigao, RZQG) and its underlying mechanisms via transdermal administration.Methods: The main components of RZQG were confirmed by gas chromatography-mass spectrometry (GC-MS). The effect of RZQG on L-type voltage-dependent calcium channel (L-VDCC) was evaluated by CaCl2- and ACh-induced contraction in isolated colon. The antidiarrheal efficacy of RZQG was further investigated by the senna-induced diarrhea mice based on the frequency of loose stools, diarrhea rate and index, fecal moisture content, and the basal tension of the colon. Additionally, the protein expression of CACNA1C, CACNA1D, cAMP, and PKA were detected with Western blot and immunohistochemistry (IHC).Results: GC-MS analysis determined 14 components in RZQG. In vitro, RZQG relaxed the CaCl2- and ACh-induced tension, while nifedipine (a L-VDCC inhibitor) and H-89 (a PKA inhibitor) decreased the relaxation. In vivo, animal model showed that transdermal administration of RZQG exhibited a significant reduction in the frequency of loose stools, diarrhea rate and index, fecal moisture content and the basal tension. Compared to the model group, the colon of mice treated with RZQG showed lower expression of CACNA1C, CACNA1D, cAMP, and PKA. IHC results showed that cAMP was downregulated in colonic smooth muscle after RZQG treatment.Conclusion: RZQG improved diarrhea symptoms and down-regulated the expression of CACNA1C and CACNA1D via transdermal administration, which is closely associated with the cAMP/PKA signaling pathway in colonic smooth muscle.Keywords: Renzhu ointment, transdermal administration, antidiarrheal effect, antidiarrheal mechanisms